2023
DOI: 10.1097/meg.0000000000002625
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between non-alcoholic fatty liver disease and fatty pancreas: a systematic review and meta-analysis

Wasit Wongtrakul,
Suvijak Untaaveesup,
Nonthalee Pausawadi
et al.

Abstract: Background Accumulating evidence suggests a potential relationship between non-alcoholic fatty liver disease (NAFLD) and fatty pancreas, as both conditions are associated with fat deposition in the liver and pancreas, respectively. The meta-analysis aimed to investigate the bidirectional association between NAFLD and fatty pancreas, as well as their respective effects on disease severity. Methods A systematic search of the EMBASE and MEDLINE databases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…In consistent with these results, our study found that among participants with NAFLD, 38.3% were nonobese and 11.9% were lean. Previous studies using liver histology or noninvasive fibrosis tests demonstrated that nonobese or lean individuals with NAFLD are also associated with an increased risk of advanced fibrosis, liver-related mortality, and even an increased risk of extra-hepatic complications, and all-cause and cardiovascular mortality [27,29]. However, no previous studies have focused on the association between NAFLD and gallstone formation in nonobese or lean individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with these results, our study found that among participants with NAFLD, 38.3% were nonobese and 11.9% were lean. Previous studies using liver histology or noninvasive fibrosis tests demonstrated that nonobese or lean individuals with NAFLD are also associated with an increased risk of advanced fibrosis, liver-related mortality, and even an increased risk of extra-hepatic complications, and all-cause and cardiovascular mortality [27,29]. However, no previous studies have focused on the association between NAFLD and gallstone formation in nonobese or lean individuals.…”
Section: Discussionmentioning
confidence: 99%